A computable extension for D-finite functions: DD-finite functions. (September 2019) - Jiménez-Pastor, Antonio; Pillwein, Veronika
Abstract: Differentiably finite (D-finite) formal power series form a large class of useful functions for which a variety of symbolic algorithms exists. Among these methods are several closure properties that can be carried out automatically. We introduce a natural extension of these functions to a larger class of computable objects for which we prove closure properties. These are again algorithmic. This extension can be iterated constructively preserving the closure properties.